(untitled) (Journal of Open Law, Technology & Society, 2009)
Now mainstream within the software market, Open Source (“OS”), which began as an ideological pursuit to create greater freedom to innovate without concern for the constraints of proprietary licences, has today achieved such a key role in software development that it may begin to enter a level of maturity in which competition law risks could arise. This is only likely to be the case in limited circumstances and probably only as a result of a potential arguments concerning anti-competitive ‘effects’ rather than any anti-competitive object. Nevertheless, it is of interest to consider how, theoretically, competition law might apply to some of the OS licensing terms in situations where the commercial contributors to code have either individually, collectively or as a result of the network effects of the OS community attained a dominant market position in a relevant market, access to which the OS code is necessary. If were to this occur, some difficult competition law questions may emerge from the success of OS and as an unintended consequence of its principally pro-competitive and efficiency enhancing objective.